2012
DOI: 10.4103/0976-237x.94557
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive atypical ameloblastic fibrodentinoma: Report of a case

Abstract: Ameloblastic fibroma and related lesions constitute a group of lesions, which range in biologic behaviour from true neoplasms to hamartomas. This group of lesions is also sometimes referred to as mixed odontogenic tumors and usually includes ameloblastic fibroma, ameloblastic fibrodentinoma and ameloblastic fibro-odontoma. Despite numerous efforts however, there is still considerable confusion concerning the nature and interrelationship of these mixed odontogenic tumors and related lesions. The malignant count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 11 publications
4
40
0
Order By: Relevance
“…In this case the lesion was associated with crown of a unerputed canine. AFD is generally seen in young adults with males more commonly affected than females with a predilection of 3:1 [7]. In the present case the child was just one-year-old.…”
Section: Discussionmentioning
confidence: 71%
“…In this case the lesion was associated with crown of a unerputed canine. AFD is generally seen in young adults with males more commonly affected than females with a predilection of 3:1 [7]. In the present case the child was just one-year-old.…”
Section: Discussionmentioning
confidence: 71%
“…Several cases of AFO have been reported in the literature (3,6,8,10,11,(13)(14)(15)(16)(17)(18)(19) and it is known to frequently affect individuals below 16 years of age (1,8,20,21). One study has indicated that, when compared with ameloblastic fibroma, AFO more commonly affects individuals belonging to the younger age group; however, this claim can be refuted (19).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, patients coming from countries such as India [19,20] or South America [11,21,22] present to dentists often at teenage or adult age whereas in countries such as Germany [23,24] or Switzerland, tumors are detected much earlier. An important explanatory reason may be the fact that the latter countries have well developed health care systems and dental examinations are offered in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…As reported above a small part of the maxillary sinus was exposed and partially involved in the surgical resection. A more aggressive treatment as described by Girradi concerning fibrodentinoma [20] is not recommended because of increased morbidity. Especially in the mandible, the risk of a pathological fracture is very high when performing a marginal resection and thus cannot be supported when compared to a more conservative procedure of tumor tissue removal [14].…”
Section: Discussionmentioning
confidence: 99%